Hubungan Antara Intensi Mengakses Media Sosial dengan Kecenderungan Fear of Missing Out pada Gen Z di Yogyakarta - Salsabila Rafif Yasirah; Andhita Dyorita Khoiryasdien (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to examine the relationship between social media usage intention and the tendency of fear of missing out (FoMO) among Gen Z in Yogyakarta. The research utilized a quantitative descriptive and inferential approach with a simple correlation method. A total of 140 Gen Z individuals aged 14–26 years in Yogyakarta participated as research subjects. Data were collected through an online survey using Google Forms, which measured social media usage intention and the tendency of fear of missing out. The survey was distributed via social media, and the data obtained were analyzed using classical assumption tests, Pearson correlation tests, and product-moment analysis. The results showed a significant positive relationship between social media usage intention and the tendency of fear of missing out among Gen Z in Yogyakarta (t = 0.694, p < 0.000). This indicates that the higher the intention to use social media, the higher the tendency for FoMO among Gen Z in Yogyakarta. Although the study was conducted effectively, it has some limitations, such as the lack of focus on a specific type of social media. Therefore, future research is recommended to consider sample balance and employ other, more comprehensive methods to strengthen the findings